Stochastic variation in the FOXM1 transcription program mediates replication stress tolerance - Hendrika A. Segeren; Kathryn A. Wierenga; Frank M. Riemers; Elsbeth A. vanLiere; Bart Westendorp (Molecular Oncology)
Oncogene‐induced replication stress (RS) is a vulnerability of cancer cells that forces reliance on the intra‐S‐phase checkpoint to ensure faithful genome duplication. Inhibitors of the intra‐S‐phase checkpoint kinases ATR and CHK1 have been developed, but resistance to these drugs remains problematic. Understanding drug tolerance mechanisms is impeded by analysis of bulk samples, which neglect tumor heterogeneity and often fail to accurately interpret cell cycle‐mediated resistance. Here, by combining intracellular immunostaining and single‐cell RNA‐sequencing, we characterized the transcriptomes of oncogenic RAS‐expressing cells with variable levels of RS when challenged with a CHK1 inhibitor combined with gemcitabine. We identified 37 genes differentially expressed between tolerant and sensitive cells, including several FOXM1 targets. While complete knockdown of FOXM1 impeded cell proliferation, partial knockdown protected cells against DNA damage, and improved recovery from drug‐induced RS. Remarkably, knockdown of individual FOXM1 target genes UBE2C and MKI67 also mitigated DNA damage, uncovering unanticipated roles for these in the replication stress response. Our results suggest that low levels of FOXM1‐dependent gene expression during S and G2 phase protects cells against excessive DNA damage during drug‐induced replication stress.